Variations in Circulating Levels of Angiopoietin-2 Over Time Are Predictive of Ramucirumab–Paclitaxel Therapy Outcome in Advanced Gastric Cancer: Results of Prospective Study - D’Alessandro, Rosalba; Refolo, Maria Grazia; Schirizzi, Annalisa; De Leonardis, Giampiero; Donghia, Rossella; Guerra, Vito; Giannelli, Gianluigi; Lolli, Ivan Roberto; Laterza, Maria Maddalena; De Vita, Ferdinando; Messa, Caterina; Lotesoriere, Claudio (Frontiers in Oncology, 2022)
The combination of paclitaxel and ramucirumab is the second-line therapy of choice in the treatment of advanced gastric cancer. To date, no biomarkers are available in gastric cancer to predict the outcome of antiangiogenic therapy. The present prospective study included 35 patients undergoing second-line therapy with ramucirumab and paclitaxel. Serum samples were systematically collected from the beginning of therapy and at each cycle until disease progression. Multiplex analysis of a panel of angiogenic factors identified markers for which the changes at defined time intervals were significantly different in patients with progression-free survival ≤3 (Rapid Progression Group) compared to those with progression-free survival >3 (Control Disease Group). Comparative analysis revealed significantly different results in the two groups of patients for VEGFC and Angiopoietin-2, both involved in angiogenesis and lymphangiogenesis. VEGFC increased in the progressive-disease group, while it decreased in the control-disease group. This decrease persisted beyond the third cycle, and it was statistically significant compared to the basal level in patients with longer progression-free survival. Angiopoietin-2 decreased significantly after 2 months of therapy. At progression time, there was a significant increase in VEGFC and Angiopoietin-2, suggesting the activation pathways counteracting the blockade of VEGFR2 by ramucirumab. Overall results showed that a greater change in VEGFC and Angiopoietin-2 levels measured at the beginning of the third cycle of therapy corresponded to a lower risk of progression and thus to longer progression-free survival.